Efektivitas Penggunaan Dana Desa - Taufik Raharjo; Agus Sunarya Sulaeman; Sriyani Sriyani (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2018)
ABSTRACT The purpose of this study is to analyze the effectiveness of the use of village funds in Tangerang District. Descriptive method is used to interpret realization data of the use of village funds in 2015 and 2017. It finds that the use of village funds still emphasize its use in physical development of the village and still a little concentrate on community empowerment for strengthening the community economy such as the establishment and development of BUMDesa. Keywoord: effectiveness, village funds